2019
DOI: 10.1192/bjo.2019.52
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patients’ and carers’ views about the clinical use of ketamine to inform policy and practical decisions: mixed-methods study

Abstract: Background Only one-third of patients with major depressive disorder achieve remission. One new and promising treatment, ketamine, may prove challenging to implement because of its abuse potential. Although clinicians' views have been sought, we need patients' views before large scale roll-out is considered. Aims To explore patients’ and carers' views to inform policy and practical decisions about the clinical use of ketamine. Method We carried out a mixed-methods study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Participants were asked for details of their history prior to being accepted to attend the focus groups and were remunerated for their time at each focus group, as well as travel expenses. Each focus group lasted between 60 and 90 min and was facilitated by two service-user researchers, using a topic guide based on the results of a public consultation day 15 (Appendix). To ensure a shared understanding, a summary of ketamine treatment for depression was provided (supplementary data, section 1 available at https:// doi.org/10.1192/bjo.2020.165).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked for details of their history prior to being accepted to attend the focus groups and were remunerated for their time at each focus group, as well as travel expenses. Each focus group lasted between 60 and 90 min and was facilitated by two service-user researchers, using a topic guide based on the results of a public consultation day 15 (Appendix). To ensure a shared understanding, a summary of ketamine treatment for depression was provided (supplementary data, section 1 available at https:// doi.org/10.1192/bjo.2020.165).…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Despite this, the National Institute for Health and Care Excellence (NICE) recently made a preliminary decision against its recommendation for several reasons including its cost-effectiveness and concerns over stopping the treatment. 13 Positive experiences of ketamine for treating depression have been reported by patients, carers and advocates 14,15 but more information is required prior to its widespread roll-out as it poses challenges that come alongside the benefits. These include the potential for misuse, dependence, tolerance, withdrawal symptoms and physiological side-effects (for example urological/bladder problems), [16][17][18] as well as the potential for illegal diversion to street markets or illegal access if a prescription is refused.…”
Section: Introductionmentioning
confidence: 99%
“…These suggestions have also been made by patients. 18 Some individuals in our study identified a need for closer monitoring and, with regard to psychological input, one participant thought that it should be provided soon after treatment-related dissociative and psychotomimetic effects have worn off because, in their experience, receptiveness will be optimised at this point because of improved mood and openness to the possibility of change.…”
Section: Impact On Suicidal Ideationmentioning
confidence: 97%
“…28 A minority of our participants thought that there might be a possibility of dependency on ketamine occurring over time. Dependency has not been identified as an adverse outcome of ketamine treatment, 27 although concerns about misuse potential have been raised, 18,[29][30][31] including risk of illegal procurement. One individual in our study referred to a possibility of purchasing street ketamine to self-medicate because it was cheaper and more locally accessible than therapeutic ketamine treatment.…”
Section: Impact On Suicidal Ideationmentioning
confidence: 99%
See 1 more Smart Citation